Serum Periostin Levels are Significantly Higher in Patients with Primary Hyperparathyroidism and Closely Related to Osteoporosis - Yigitdol, Ismail; Gulumsek, Erdinc; Ozturk, Huseyin Ali; Arici, Fatih Necip; Akbal, Kubilay; Pirinci, Okan; Karacay, Mert; Cihan, Tutku Naz; Totik, Zeynep Gizem; Akyildiz, Mustafa Aykut; Avci, Begum Seyda; Avci, Akkan; Sumbul, Hilmi Erdem (Experimental and Clinical Endocrinology & Diabetes, 2023)
Background Periostin is an emerging biomarker that plays a role in bone metabolism and may be associated with bone mineral density (BMD). This study is aimed to investigate serum periostin levels in patients with primary hyperparathyroidism (PHPT) and its correlation with BMD in these patients.Methods Forty patients with newly diagnosed PHPT without co-morbidities and 30 healthy controls were included. Laboratory tests for the diagnosis of PHPT and serum levels of periostin were measured for all patients. BMD was measured on lumbar spines L1 and L4 by dual-energy X-ray absorptiometry (DEXA). Serum periostin levels were detected using an enzyme-linked immunosorbent assay (ELISA).Results Serum periostin levels were significantly higher in patients with PHPT than in healthy controls (p<0.001). Serum periostin levels were also significantly higher (mean 59.7±11.0 ng/mL) in PHPT patients with osteoporosis than those without osteoporosis (p=0.004). In logistic regression analysis, only serum periostin levels independently predicted the patients with osteoporosis. According to this analysis, every 1 ng/mL increase in serum periostin increased the risk of having osteoporosis by 20.6%. When the cut-off for serum periostin level was 49.75 ng/mL, the patients with osteoporosis were predicted with 71.4% sensitivity and 69.2% specificity. Multivariate regression analysis revealed a negative correlation between serum periostin levels and L1-L4 T scores on DEXA.Conclusion This is the first study to determine that serum periostin levels are higher in PHPT patients than those without PHPT and to demonstrate a significant association between serum periostin levels and T scores on DEXA in patients with PHPT. These findings will aid in detecting osteoporosis in patients with PHPT and making the decision for surgery in PHPT patients with no need for DEXA imaging that involves radiation.
Keywords: primary hyperparathyroidism; periostin; osteoporosis; bone mineral density